2022
DOI: 10.1039/d2nj04233a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental insights into the properties of donor–σ–acceptor type derivatives of quinoxaline and methanone containing different donor moieties

Abstract: A strategy of fused electron accepting moieties was employed to synthesise a series of donor-substituted quinoxaline–methanone derivatives as red TADF emitters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The energy gap between the singlet and triplet states (Δ E S–T ) was calculated as the energy difference between S 1 and T 1 excited states having the ground state geometry in THF. Previously we have shown that the described approach allows the accurate reproduction of the electronic structures in the ground and excited states of BODIPY dyes, 21 derivatives of quinoxaline with dimethylacridine, carbazole and phenothiazine as donor moieties 22 and molecular glasses based on 1,8-naphthalimide and triphenylamine moieties. 23 All of the calculations were carried out using the Gaussian 16 program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy gap between the singlet and triplet states (Δ E S–T ) was calculated as the energy difference between S 1 and T 1 excited states having the ground state geometry in THF. Previously we have shown that the described approach allows the accurate reproduction of the electronic structures in the ground and excited states of BODIPY dyes, 21 derivatives of quinoxaline with dimethylacridine, carbazole and phenothiazine as donor moieties 22 and molecular glasses based on 1,8-naphthalimide and triphenylamine moieties. 23 All of the calculations were carried out using the Gaussian 16 program.…”
Section: Resultsmentioning
confidence: 99%
“…They are in agreement with the results of earlier investigation, which allowed us to conclude that despite M062X providing accurate reproduction of the absorption spectra in terms of both intensity and the relative peak position, 16,25,26 this functional in most cases underestimates the wavelengths of absorption maxima. 21–23,29,30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last three functionals are referred to as one of the most accurate for calculating UV–vis spectra of organic molecules and have been successfully applied by us in the study of absorption and emission properties of various organic molecules. In addition, we have calculated the characteristics of PHES using double hybrid SOS-wPBEPP86 functional, which was developed specifically for accurate calculation of the energy of excited states. SOS-wPBEPP86/def2-TZVP calculations have been performed using ORCA5 software .…”
Section: Computational Detailsmentioning
confidence: 99%